1999
DOI: 10.7326/0003-4819-131-6-199909210-00002
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Nocturnal Hemoglobinuria Cells in Patients with Bone Marrow Failure Syndromes

Abstract: Flow cytometric analysis is superior to the Ham test and permits concomitant diagnosis of PNH in about 20% of patients with myelodysplasia (a rate similar to that seen in patients with aplastic anemia). The presence of GPI-anchored protein-deficient cells in myelodysplasia predicts responsiveness to immunosuppressive therapy. Early emergence of GPI-anchored protein-deficient hematopoiesis in a patient with marrow failure may point to an underlying immune pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
190
6
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(207 citation statements)
references
References 36 publications
8
190
6
3
Order By: Relevance
“…The presence of a PNH clone was determined by flow cytometry if 41% of GPI-AP-deficient circulating neutrophils, defined by negativity for surface staining for CD66b and CD16, were present as a distinct population of CD15 þ cells. 19 Patients were categorized as hemolytic PNH or AA/PNH based on clinical evidence of marked hemolysis (elevated LDH, plasma and urine hemoglobin, reticulocytosis) or a history or manifestations of marrow failure 20 (platelet counts o50 000/ml, neutrophil counts o1000/ml), respectively. At the time of sampling, none of the patients were actively infected.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…The presence of a PNH clone was determined by flow cytometry if 41% of GPI-AP-deficient circulating neutrophils, defined by negativity for surface staining for CD66b and CD16, were present as a distinct population of CD15 þ cells. 19 Patients were categorized as hemolytic PNH or AA/PNH based on clinical evidence of marked hemolysis (elevated LDH, plasma and urine hemoglobin, reticulocytosis) or a history or manifestations of marrow failure 20 (platelet counts o50 000/ml, neutrophil counts o1000/ml), respectively. At the time of sampling, none of the patients were actively infected.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…17 Since PNH clones have been identified in 10% to 25% of patients with a diagnosis of MDS, flow cytometry aiming to identify such clones is increasingly becoming part of the work up of MDS. [17][18][19] As in MDS, evolution of PNH to leukemia is possible (reviewed in Ref. 20), although with a much lower frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, MDS bears some similarity to AA and PNH in that some MDS patients will also respond to immunosuppression. 18,21 If expansion of the PNH cell population takes place by virtue of selection in favor of the PIG-A mutant clone(s) in an aplastic environment, this mechanism might or might not still operate after the PNH cell population is detected. 12 If it does, then the PNH cell population would continue to expand; if it does not, then the PNH cell population would remain stable or perhaps even regress, thanks to relaxation of selection.…”
Section: Introductionmentioning
confidence: 99%
“…12,[15][16][17] The proportions of GPI-deficient cells in AA and MDS patients varied greatly (0.003-99%) and were usually lower than those in PNH patients. [5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, PIG-A mutations have partially been reported in patients with AA, 11,18 AA/PNH, 3,19 and MDS. 15,17 However, it could not be ruled out that these AA and MDS patients analyzed for PIG-A gene abnormality are actually PNH, because the AA and MDS patients had 2.4-28.5% and 1.19-22% of GPI-negative erythrocytes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, several researchers reported that 15-88.6% of untreated and/or treated AA patients have GPIdeficient cells [5][6][7][8][9][10][11][12][13][14] as do 10-23% of MDS patients. 12,[15][16][17] The proportions of GPI-deficient cells in AA and MDS patients varied greatly (0.003-99%) and were usually lower than those in PNH patients. [5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, PIG-A mutations have partially been reported in patients with AA, 11,18 AA/PNH, 3,19 and MDS.…”
Section: Introductionmentioning
confidence: 99%